1999
DOI: 10.1099/00207713-49-4-1725
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetic evidence for the transfer of Eubacterium lentum to the genus Eggerthella as Eggerthella lenta gen. nov., comb. nov.

Abstract: Phylogenetic evidence for the transfer ofEubacterium lentum has unique phenotypic characters within the genus Eubacterium. The 165 rRNA sequence of Eubaderium lentum was determined and its phylogenetic position was defined. This micro-organism is a member of the genus Eubacterium but it is not closely related to Eubacterium limosum, the type species of the genus Eubacterium, and is nearer to Collinsella aerofaciens and Coriobacterium glomerans. A PCR-based identification system using species-specif ic primers … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
71
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(72 citation statements)
references
References 20 publications
0
71
1
Order By: Relevance
“…Thorasin, L. Hoyles and A. L. McCartney However, it is noteworthy that our Eggerthella API 20 A data clearly indicated that, with the exception of the type strain, all strains were saccharolytic. These findings contradict previously published data, including the species description of E. lenta, which suggest that E. lenta is generally unreactive in typical phenotypic laboratory tests and is asaccharolytic (Eggerth, 1935;Moore et al, 1971;Kageyama et al, 1999b;Wade et al, 1999). This most likely reflects the fact that all steps of the phenotypic characterization work performed in this study were carried out in an anaerobic cabinet, as opposed to manipulations being done on the laboratory bench and incubations in anaerobic gas jars (which take up to 1 h to reduce the atmospheric conditions if using gas-generating sachets).…”
Section: T Thorasin L Hoyles and A L Mccartneycontrasting
confidence: 57%
“…Thorasin, L. Hoyles and A. L. McCartney However, it is noteworthy that our Eggerthella API 20 A data clearly indicated that, with the exception of the type strain, all strains were saccharolytic. These findings contradict previously published data, including the species description of E. lenta, which suggest that E. lenta is generally unreactive in typical phenotypic laboratory tests and is asaccharolytic (Eggerth, 1935;Moore et al, 1971;Kageyama et al, 1999b;Wade et al, 1999). This most likely reflects the fact that all steps of the phenotypic characterization work performed in this study were carried out in an anaerobic cabinet, as opposed to manipulations being done on the laboratory bench and incubations in anaerobic gas jars (which take up to 1 h to reduce the atmospheric conditions if using gas-generating sachets).…”
Section: T Thorasin L Hoyles and A L Mccartneycontrasting
confidence: 57%
“…The only nonbifidobacterial species that showed PA ELISA reactivity was Eubacterium lentum. This species, which is one of the predominant microorganisms from the human intestine, has been reclassified as Eggerthella lenta (19). In contrast to other eubacteria, which belong to the low-GϩC group, this bacterium has a high GϩC content and by definition a lipoglycan instead of an LTA (31).…”
Section: Resultsmentioning
confidence: 99%
“…lenta by phylogenic identification. 11) In this study, we determined phylogenic affiliation of E. sp. SDG-2 with 16S rRNA gene-based identification using polymerase chain reaction with proper primers.…”
mentioning
confidence: 99%